2019
DOI: 10.1007/s12182-019-0349-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative desulfurization of diesel fuel oil using supported Fenton catalysts and assisted with ultrasonic energy

Abstract: An ultrasound-assisted heterogeneous catalytic oxidation process was applied to eliminate sulfur from commercial diesel fuel oil. The studied variables were catalyst concentration, type of catalyst (homogeneous or heterogeneous), oxidizing agent concentration, and the application of ultrasound energy. Supported catalysts were prepared by impregnation of coal fly ash with an iron(II) sulfate aqueous solution using ultrasound energy. After drying, the catalyst was calcined at 500 °C for 4 h. The oxidizing agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…Nanoparticles improve the adsorption of sulfur compounds due to their large surface area [53] . Photocatalyst under UV [54] or visible light [55] , nano-sized silica particles including mesoporous silica [56] , aluminum oxide particles [57] , transition metal oxides [58] , activated carbons [59] , modified metal–organic frameworks [60] , Ni catalyst also called sponge metal [61] , nanocomposite [62] , graphene oxide [63] , activated carbon (AC)-supported phosphotungstic acid [64] and fly ash-modified fenton catalysts [65] are used. In the case of using heterogeneous catalysts, the catalytic ODS mechanism [66] , [67] , [68] , [69] , [70] is illustrated in Scheme 1 .…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanoparticles improve the adsorption of sulfur compounds due to their large surface area [53] . Photocatalyst under UV [54] or visible light [55] , nano-sized silica particles including mesoporous silica [56] , aluminum oxide particles [57] , transition metal oxides [58] , activated carbons [59] , modified metal–organic frameworks [60] , Ni catalyst also called sponge metal [61] , nanocomposite [62] , graphene oxide [63] , activated carbon (AC)-supported phosphotungstic acid [64] and fly ash-modified fenton catalysts [65] are used. In the case of using heterogeneous catalysts, the catalytic ODS mechanism [66] , [67] , [68] , [69] , [70] is illustrated in Scheme 1 .…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
“…Since homogeneous Fenton catalysts (FeSO 4 ) dissolve in the aqueous phase and consequently, making their recovery difficult [140] after ODS reactions, water-insoluble Fenton-like catalysts supported on coal fly ash (which is a very cheap waste from coal-fired power plants) were synthesized [141] . Approximately 30% desulfurization was carried out as a result of simultaneous oxidation and extraction of sulfur compounds from commercial diesel fuel containing 595 ppm S using 10 wt% H 2 O 2 and ethanol solvent in the presence of the Fenton-like catalyst in an ultrasonic bath at 47 kHz frequency and 147 W power [65] . It has been suggested that the oxidation stems from the hydroxyl radicals formed from the reaction between Fe 2+ and H 2 O 2 .…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure achieved remarkably performances in the degradation of benzothiophene [34] and desulphurization of diesel-like fuels [35] by using nanostructured catalysts. Nonetheless, these systems were produced by using unfriendly procedures and lead to the merely deposition of the iron nanoparticles onto the support surface.…”
Section: Introductionmentioning
confidence: 99%